Antibody responses of SARS-CoV-2 vaccines amongst health care workers in a tertiary care hospital in Tripura, India: A cross-sectional study - Chanda Mog; Sibabrata Bhattacharya; Subrata Baidya; Shampa Das (Wolters Kluwer Medknow Publications, 2022)
Background: Vaccines against COVID-19 plays an important role in limiting the spread of SARS-CoV-2 infections and also in curbing mortality and morbidity due to COVID-19. Objective: To estimate the anti-spike antibody response after receiving the second dose of SARS-CoV-2 vaccines amongst health care workers of a tertiary care hospital in Tripura, India. Materials and Method: A cross- sectional study was conducted from 1 July to 20 August 2021 at Agartala Government Medical College and GBP Hospital, Agartala among 561 health care workers who had received first and second doses of SARS-CoV-2 vaccines and had completed 14 days after receiving the second dose. Results: The present study showed that health care workers who had received both doses of COVID-19 vaccine had 99.5% seropositivity to anti-spike antibody. The median SARS-CoV-2 anti-spike antibody titter was 250 with an IQR (211.55-250). Seropositivity rate was higher among Covishield recipients (99.8% [550/551]) as compared to Covaxin recipients (80% [8/10]) and it was found to be statistically significant (P = 0.000). Conclusion: The present study suggests that a good immune response was elicited against spike antigen of SARS-CoV-2 after two complete doses of Covishield (ChAdOx1-nCoV-19) or Covaxin (BBV152).